INTERNATIONAL ENGLISH EXAMS IN THE CONTEXT OF INTERNATIONALIZATION OF EDUCATIONAL SERVICES - Lysa, Nataliya; Semenchuk, Yulian (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
The internationalization of education is an important factor for the development and implementation of innovations in the educational sector, for increasing competitiveness in the educational service market within globalization. Knowledge of foreign languages expands the range of international cooperation in various fields and contributes to the study of foreign experience, allows the use of internship opportunities at universities in other countries, gives advantages to teachers in hiring or enrolling in training for students. The instrument of internationalization is international exams, which allow you to receive a certificate confirming the level of proficiency in a foreign, primarily English, language. The article analyzes the state of internationalization of educational services in terms of organizing and conducting international examinations in English. The structure and the constituent parts of the tests, which are most often passed by applicants for obtaining a certificate, are characterized and analyzed. The features of international exams are considered and the points that should be guided by when performing test tasks are highlighted.